Упростить выражение cos(90-a)+sin(180-a)
cos(90-a)+sin(180-a) = Sina+Sina = 2 Sina
Пояснение
по формулам приведения:
Cos(90-a)=+Sina
Sin(180-a)=+Sina
заменяем:
+Sina+Sina
получаем:
2Sina
cos(90-a)+sin(180-a)=sin a+ sin a= 2*sin a
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
cos(90-a)+sin(180-a) = Sina+Sina = 2 Sina
Пояснение
по формулам приведения:
Cos(90-a)=+Sina
Sin(180-a)=+Sina
заменяем:
+Sina+Sina
получаем:
2Sina
cos(90-a)+sin(180-a)=sin a+ sin a= 2*sin a